β-aminoisobutyrics acid, a metabolite of BCAA, activates the AMPK/Nrf-2 pathway to prevent ferroptosis and ameliorates lung ischemia-reperfusion injury - Ziyue Zhang; Xingbing Li; Jingwen Guo; Bo He; Lianpan Wu; Rongpei Yang; Xingyue Li; Dandong Fang; XiaoLi Yang; Donghai Yang; Fengxian Wang; Ming Tang; et al. (Molecular Medicine, 2023)
Abstract Background Lung ischemia-reperfusion (I/R) injury is a serious clinical problem without effective treatment. Enhancing branched-chain amino acids (BCAA) metabolism can protect against cardiac I/R injury, which may be related to bioactive molecules generated by BCAA metabolites. L-β-aminoisobutyric acid (L-BAIBA), a metabolite of BCAA, has multi-organ protective effects, but whether it protects against lung I/R injury is unclear. Methods To assess the protective effect of L-BAIBA against lung I/R injury, an animal model was generated by clamping the hilum of the left lung, followed by releasing the clamp in C57BL/6 mice. Mice with lung I/R injury were pre-treated or post-treated with L-BAIBA (150 mg/kg/day), given by gavage or intraperitoneal injection. Lung injury was assessed by measuring lung edema and analyzing blood gases. Inflammation was assessed by measuring proinflammatory cytokines in bronchoalveolar lavage fluid (BALF), and neutrophil infiltration of the lung was measured by myeloperoxidase activity. Molecular biological methods, including western blot and immunofluorescence, were used to detect potential signaling mechanisms in A549 and BEAS-2B cells. Results We found that L-BAIBA can protect the lung from I/R injury by inhibiting ferroptosis, which depends on the up-regulation of the expressions of GPX4 and SLC7A11 in C57BL/6 mice. Additionally, we demonstrated that the Nrf-2 signaling pathway is key to the inhibitory effect of L-BAIBA on ferroptosis in A549 and BEAS-2B cells. L-BAIBA can induce the nuclear translocation of Nrf-2. Interfering with the expression of Nrf-2 eliminated the protective effect of L-BAIBA on ferroptosis. A screening of potential signaling pathways revealed that L-BAIBA can increase the phosphorylation of AMPK, and compound C can block the Nrf-2 nuclear translocation induced by L-BAIBA. The presence of compound C also blocked the protective effects of L-BAIBA on lung I/R injury in C57BL/6 mice. Conclusions Our study showed that L-BAIBA protects against lung I/R injury via the AMPK/Nrf-2 signaling pathway, which could be a therapeutic target.